Development of clothing size for pre school children based on anthropometric measurements - Bari, Siti Balkis; Mohd Salleh, Naimah; Sulaiman, Norhasmah; Othman, Mumtazah (Australian Academy of Business and Social Sciences, 2014)
Anthropometric data play an important role in creating garment sizing system. The purpose of this study is to examine anthropometric measurements among pre-school children for develop garment sizes. Ill-fitting clothes among children in Malaysia resulted in this study. This study was carried out in 11 kindergartens in Kota Tinggi, Johor. A total number of 220 respondents were surveyed. Respondents consisted of 107 boys and 113 girls. Respondents’ background and respondents’ measurements were obtained using a questionnaire. The anthropometric data were analysed using SPSS program. Independent sample t-test was used to identify differences between sexes. Descriptive statistic found that the respondents had moderate body size. A sizing system to cover garment for pre-school students was developed based on anthropometric data. Three sizes were developed: S (small), M (medium) and L (large). Anthropometric survey should be done in population to get an accurate garment sizing. Garment will not fit on the body if the size is inaccurate with the body. This study will be useful for provide a better quality of fit in the garment construction.